2017
DOI: 10.1007/s00068-017-0775-9
|View full text |Cite
|
Sign up to set email alerts
|

Radial nerve palsy in humeral shaft fractures with internal fixation: analysis of management and outcome

Abstract: IntroductionThe incidence of radial nerve injury after humeral shaft fractures is on average 11.8% (Shao et al., J Bone Jt Surg Br 87(12):1647–1652, 2005) representing the most common peripheral nerve injury associated with long bone fractures (Korompilias et al., Injury, 2013). The purpose of this study was to analyze our current policy and long-term outcome, regarding surgically treated humeral shaft fractures in combination with radial nerve palsy.Materials and methodsWe retrospectively analyzed the data of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 22 publications
2
61
0
8
Order By: Relevance
“…Previous studies have demonstrated iatrogenic radial nerve injuries occur in 6-32% of plated humeral shaft fractures. [5][6][7][8][9] None were observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated iatrogenic radial nerve injuries occur in 6-32% of plated humeral shaft fractures. [5][6][7][8][9] None were observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A “secondary radial palsy” during fracture manipulation or reduction can occur as a result of intraoperative nerve exploration or the surgical approach used [ 13 ]. The radial nerve is extremely sensitive to even slight tension exerted during surgical exploration of the fracture.…”
Section: Reviewmentioning
confidence: 99%
“…The radial nerve is extremely sensitive to even slight tension exerted during surgical exploration of the fracture. The position of the patient during general anesthesia is also a causative factor as loss of muscle tone can lead to inadvertent traction at the fracture site and compression of the radial nerve [ 13 ]. For the most part, radial nerve entrapment is seen after fracture manipulation when the nerve is unknowingly entrapped between bone and an installed plate, compressed by a bone fragment or if excessive nailing of the bone occurs [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
“…In humerus fractures, RNI is common due to the mechanism of fracture formation and the sharpness of fracture ends. In addition, RNI is a common case during fracture surgery [2,3,4]. Since the radial nerve is located in the intermuscular area, it is easily affected by tension caused by loosening or pulling during surgery (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Since the radial nerve is located in the intermuscular area, it is easily affected by tension caused by loosening or pulling during surgery (Figure 2). Besides, abnormal movements cause nerve strain and nerve injury due to the patient's inability to control his/her arm after anesthesia [4][5][6]. For this reason, it is very important for the assistant health personnel to be attentive in the surgery of distal humerus fractures.…”
Section: Discussionmentioning
confidence: 99%